Biomarkers Of Hypoxia In Chronic Rhinosinusitis: Pathophysiological And Diagnostic Implications (Eurasian Journal of Humanities and Social Sciences, 2025)
Chronic rhinosinusitis (CRS) is a complex inflammatory disease of the sinonasal mucosa, affecting approximately 10-12% of the adult population worldwide and significantly impairing quality of life. A hallmark of CRS pathogenesis is the development of local hypoxia caused by ostial obstruction, mucosal swelling, and inflammation-induced vascular remodeling. Hypoxia acts both as a consequence and amplifier of chronic inflammation, contributing to epithelial barrier disruption, immune dysregulation, and tissue remodeling. This review focuses on the interplay between hypoxia and inflammation in CRS and highlights key hypoxia-related biomarkers such as hypoxia-inducible factor-1 alpha (HIF1α), vascular endothelial growth factor (VEGF), mucin 5AC (MUC5AC), reactive oxygen species (ROS), high-mobility group box 1 (HMGB1), interleukin-8 (IL-8), and epithelial tight junction proteins (ZO-1, E-cadherin). These biomarkers reflect the underlying molecular mechanisms that sustain the chronic inflammatory state and have potential diagnostic and prognostic utility. Their evaluation may aid in patient phenotyping, monitoring disease progression, and tailoring personalized therapies. Further research is needed to standardize biomarker assessment and validate their clinical relevance in CRS management